PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PADA BANK SYARIAH INDONESIA CABANG VETERAN SURAKARTA - ilhamkarin ilhamkarin (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
This study aims to analyze the influence of service quality, trust to customer loyalty at Bank Syariah Indonesia Veteran Surakarta Branch. The sample in this study amounted to 100 customers of Bank Syariah Indonesia Veteran Surakarta branch. Bank using a questionnaire for data collection. The sampling technique is a non probability sampling method. Data analysis techniques using multiple linear regression analysis. The results of this study indicate that: Service quality, trust have a significant influence on customer loyalty.